Childrenâs Perception on Their Quality of Life Around Merapi Volcano - Risye Dwiyani; Norio Okada (Journal of Regional and City Planning, 2009)
Sebagai bagian dari sebuah komunitas yang berbagi ruang yang sama dengan beragam kepentingan, anak-anak dan suara mereka patut diperhitungkan dalam komunitas tersebut. Dunia mereka berbeda dengan dunia orang dewasa, sehingga pandangan mereka tidak boleh diabaikan. Studi ini difokuskan pada kehidupan anak-anak di sekitar Gunung Merapi dengan meneliti hal-hal yang membuat mereka bahagia atau tidak bahagia untuk tinggal di desa mereka. Studi ini bertujuan untuk mengidentifikasi factor-faktor yang mempengaruhi perasaan mereka terhadap hidup mereka untuk mengungkapkan potensi dan permasalahan yang ada di desa mereka. Pengumpulan data melibatkan 94 (sembilan puluh empat) anak kelas 5 dan 6 SD di 3 (tiga) desa terdekat dengan wilayah Gunung Merapi. Perasaan anak-anak diungkapkan melalui gambar dan wawancara. Disimpulkan bahwa sebagian besar perasaan anak-anak tentang kehidupan mereka berkaitan dengan keberadaan gunung berapi. Selain keberadaan gunung berapi, faktor-faktor lain yang mengancam adalah serangan hewan dan kerusakan lingkungan karena aktivitas penambangan pasir yang tak terkendali.Kata kunci: anak-anak, Gunung Merapi, perasaan, kehidupan As part of a community who live in the same shared space with various interests, children and their voices need to be taken into account in the community. Their worlds are different from that of adults, thus their views should not be overlooked. This study focuses on the life of children near Merapi volcano, one of the most active volcanoes in Indonesia, by exploring on what makes them feel happy and unhappy about living in their village. It aims to identify the factors affecting their feeling towards their lives in order to reveal current potentials and problems of the villages around Merapi from children's points of view. The data collection involved 94 children from 5th and 6th grades elementary school of three upper-most villages in Merapi volcano area of Yogyakarta Province, Indonesia. Children's feelings were expressed through drawings and followed up by interviews. It was found that many of the children's feelings about their lives were related to the existence of the volcano, both in positive and negative ways. Besides the existence of the volcano, other factors were also found threatening according to children, such as the animal attacks and environmental degradation due to uncontrolled sand mining activities.Keywords: children, Merapi volcano, feeling, life